Development of diastolic heart failure in a 6-year follow-up study in patients after acute myocarditis. Issue 9 (5th December 2010) - Escher, Felicitas; Westermann, Dirk; Gaub, Regina; Pronk, Johannes; Bock, Thomas; Al-Saadi, Nidal; Kühl, Uwe; Schultheiss, Heinz-Peter; Tschöpe, Carsten
Abstract : Background: The aim of this study was to analyse the long-term prognosis of patients with acute myocarditis (AMC) who had been discharged from hospital while having normal left ventricular (LV) function. Methods and results: 50 patients with acute myocarditis who underwent endomyocardial biopsies (EMBs) were prospectively studied. Their clinical condition was examined during a mean follow-up period of 72 (54–78) months, including tissue Doppler imaging (TDI). 4% (2/50) died, and 6% (3/50) developed dilated cardiomyopathy. 45/50 (90%) showed a normal or improvement in LV function over time. In the course of the follow-up, 49% (22/45) suffered from heart failure symptoms despite a normal ejection fraction (HFNEF). This was associated with an abnormal E/A ratio, an impaired deceleration time of early mitral flow velocity and isovolumic relaxation time, and a pathological increase in the LV filling index E/E′, in contrast to patients without heart failure symptoms (E/E′septal 10.9 (9.3–13.8) vs 6.8 (6.4–9.1); p=0.001). Plasma N-terminal proB-type natriuretic peptide levels were increased threefold in patients with HFNEF (19.9 (10.6–24.1) vs 7.3 (4.2–11.9) pmol/l; p=0.006). Conclusions: It is assumed that the evidence for AMC is associated not only with the risk of developing LV dilatation but also with an increased risk of symptomatic diastolic dysfunction after several years.